Optimizing the use of ai in elementary school learning: For teachers in the digital era - Fadli, Muhammad Rijal; Santosa, Imam; Alfian, Alfian; Syofyan , Harlinda; Fatonah, Khusnul (Jurnal Pembelajaran Pemberdayaan Masyarakat (JP2M), 2025)
The digital era requires teachers to have competence in utilizing technology, including artificial intelligence (AI), in the learning process. However, there are still many elementary school teachers who do not understand and implement AI optimally. Therefore, this Community Service activity aims to improve teachers' understanding and skills in using AI as a learning medium through interactive workshops. The community service method used in this activity is Participatory Action Research (PAR), which was carried out at State Elementary School Pejuang 7 Bekasi involving 31 teachers. The success evaluation is conducted through a pre-test before the training and a post-test after the training by measuring several key aspects, namely: (1) understanding of AI concepts in education, (2) technical skills in operating AI-based platforms, and (3) the ability to design AI-based learning strategies. The results of community service showed an increase in teachers' understanding of AI by 31%, which was shown through the difference in pre-test and post-test results. Before the workshop, most teachers did not understand AI in learning. Still, after the workshop, teachers were better able to integrate AI as a tool in designing more interactive and innovative learning. Optimizing the use of AI in elementary schools can contribute to improving the quality of learning that is more effective, interesting, and in accordance with current developments.